THE ROLE OF BEHAVIORAL THEORY IN THE RESEARCH OF MSMEs TAX COMPLIANCE IN INDONESIA - Arham, Amardianto; Firmansyah, Amrie (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2021)
This study aims to map determinants and analyze behavioral theory's role in the tax compliance of MSMEs in Indonesia to provide recommendations for future research agendas. This study uses a qualitative method with a bibliographic approach. This research object comprises 37 research articles published by Sinta accredited journals or Scopus indexed journals from 2014 to early October 2020. The results show that the most widely used behavioral theories are planned behavior and attribution theory. Meanwhile, the most tested determinants are tax knowledge, tax sanctions, and taxpayer awareness. The role and linkages of behavioral theory with several independent variables that still suggest various test results and several independent variables that are rarely tested both in Indonesia and in the international context are recommendations for future research agendas.